Fecundity Study of Spodoptera exigua (Hübner) (Lepidoptera: Noctuidae) on Various Host Plants - Azidah, A.A.; Sofian-Azirun, Mohd (2006)
This study has shown that the S. exigua female fecundity was influenced by the host plant which was fed during the larval stage. The number of eggs laid by the female when larvae were fed on shallot was higher than lady's finger. Whereas S. exigua reared on cabbage and long beans laid intermediate number of eggs. Further, the female pupal weight was also influenced by the host plant which was fed during the larval stage. The female pupal weight was heavier when larvae were fed on shallot than on cabbage and lady's finger, whilst long beans was intermediate. Furthermore, there are significant relationships between female pupal weight and adult fecundity. Â© 2006 Academic Journals Inc.